Kontrol Diri Santri Putri Jenjang Pendidikan SMP di Pondok Pesantren - Aliyah, Septa Nikmatil; Sutoyo, Anwar (Universitas Negeri Semarang, 2016)
The research was conducted based on the phenomenon that occurs in women students junior boarding school education who have behavioral violation of the rules set boarding school. This study aims to determine how the image of self-control education junior high school female students in Pondok Pesantren Al-Muayyad Surakarta and its aspects and factors that influence it. This type of research is qualitative case study design. The research location in Pondok Pesantren Al-Muayyad Surakarta. Data collection techniques used were interviews, observation, documentation. Techniques of analysis using models Miles and Huberman. Testing the validity of the data using the techniques of observation and triangulation source persistence. The results show the subject's self-control is influenced by factors vary with the subject's motivation to enter in boarding school and peer influences that are subjects that have weak and strong self-control. Location of the boarding school in the urban influence on the behavior of which is owned by the students. The conclusions in this study found three self-contained control on women students junior high school education that is against the rules of self-control, self-control and self-control against the norms of the social conditions. The most important factor is the subject of self-control forming peers.